Tom Clancy's Jack Ryan. Season three [videorecording (DVD)] - Cuse, Carlton; Roland, Graham, 1979- (Paramount, 2023)
In Season Three of Tom Clancy's Jack Ryan, Jack races against time and across Europe to stop a rogue faction within the Russian government from restoring the Soviet Empire and starting World War III.